Validation of contralateral premolars as the substrate for endodontic comparison studies. (20th February 2018) - Johnsen, G. F.; Sunde, P. T.; Haugen, H. J.
Abstract: Aim: To use micro‐CT technology and metrology software to validate the use of contralateral premolars as samples in endodontic comparison studies by comparing them before and after canal instrumentation with one instrumentation system. Furthermore, to determine whether contralateral premolar roots (CPRs) will yield non‐significantly different outcomes regarding shaping ability (volume), degree of twisting and three‐dimensional shape changes. The null‐hypothesis (H0 ) is that there are no differences between the CPRs pre‐ or post‐instrumentation. Methodology: Twenty‐eight extracted human contralateral premolars ( n  = 44 contralateral roots) from 12 donor patients were scanned with microcomputed tomography before and after instrumentation. Root canal lengths (RCLs) were measured visually using a dental‐operating microscope, electronic apex locator and micro‐CT scans. Data were analysed statistically for differences between pre‐ and post‐instrumentation. Results: Instrumentation increased the volume of the canals significantly ( P  < 0.05). Degree of twisting for a majority (83%) of the contralateral roots pairs did not change significantly ( P  > 0.05). There was no significant difference ( P  > 0.05) in the shape deviation analysis between contralateral pairs. There was no significant difference ( P  > 0.05) for RCL between the contralateral pairs for any of the three endometric methods. Conclusion: Contralateral premolar root canals were associated with similar changes in terms of volume, three‐dimensional shape and degree of twisting from pre‐ to post‐instrumentation. There was no difference between the CPR pairs pre‐ and post‐instrumentation, and the study validates contralateral premolars as samples for root canal comparison studies. The null‐hypothesis (H0 ) could not be rejected.